Comparison of Selection for Employee Position Recommended MCDM-AHP, SMART and MAUT Method - Akmaludin, Akmaludin; Sihombing, Erene Gernaria; Dewi, Linda Sari; Rinawati; Arisawati, Ester (Sinkron : jurnal dan penelitian teknik informatika, 2023)
In a company, employees are high-value assets, therefore it is necessary to select employees for the continuity of the company, of course, by getting quality human resources. The purpose of this paper is to refute the difference in the number of rankings in selecting the best employees through a comparison of the SMART and MAUT methods. Many methods can be used in the selection process. This article describes in detail about the selection of employee promotions using the MCDM-AHP collaboration method which is used to provide an assessment of the main criteria through eigenvector values ​​based on joint decisions by company leaders based on consistent and optimal questionnaire instrumentation which is not set based on percentages manually based on wishes leader. The SMART method is used to provide a sub-criteria assessment based on a balanced weighting utility according to the number of criteria used, with an assessment weight starting from zero as the lowest value and one as the highest value. The MAUT method will be used as a comparison against the results of the SMART method, where the MAUT method has differences in determining the weights on the sub-criteria based on the perception of understanding the criteria, so that they are arranged in an orderly manner and then determine the utility value of the criteria, so that there are similarities between the two methods. The ranking results obtained from the comparison of the two methods are that they have the same rating, so that the decision support taken also has similarities between the two SMART methods and the MAUT method. This can happen if the standard of measurement is carried out consistently through the MCDM-AHP method by not changing the assessment range in determining the interval range of each criterion.